Excellent Nursing Leadership Towards Magnet Culture Among Nurse Leaders: An Interview Study - Nurmeksela, Anu; Tervo-Heikkinen, Tarja; Junttila, Kristiina; Heikkilä, Asta; Kaunonen, Marja; Kortteisto, Tiina; Peltokoski, Jaana; Salmela, Susanne; Suhonen, Riitta; Kvist, Tarja (WILEY, 2025)
Aims This study describes nurse leaders' experiences of nursing leadership in Finland towards Magnet hospital culture.DesignThis is a qualitative descriptive study.
Methods The data from nurse leaders (n = 9) were collected in face-to-face or online interviews in June and August 2023 in Finland and analysed using an inductive content analysis approach.
Results Excellent nursing leadership consists of possibilities for impact, the determination of responsibilities, strong leadership in the organisation, interpersonal leadership, the empowerment of nurses' excellence and nursing leadership development. In addition, excellent nursing leadership creates the basis for development structures and nurses' participation in a Magnet culture framework.
Conclusion Excellent nursing leadership requires ability and opportunities for impact, clear responsibilities and strong interpersonal competencies so that nurses are empowered to strive for excellence. Strong nursing leadership is needed to enable functioning structures that produce efficient processes that can be used to maintain and develop the quality of nursing work in the direction of Magnet culture.
Implications for the Profession Nurse leaders' status and power must be recognised and legislated as equally as those of other professional leaders in social and health care.
Impact This study addresses nurse leaders' remarkable role in nursing development towards Magnet hospital culture. At the same time, it discusses their uncertain position in the decision-making process of the organisation.
Reporting Method COREQ guidelines were used in reporting.
Patient or Public Contribution None.